Biopsychosocial Approaches to Understanding Health in South Asian Americans (Cross-Cultural Research in Health, Illness and Well-Being,, 2018)
This volume is the first comprehensive and interdisciplinary text to holistically improve understanding of the health of South Asians residing in the United States by considering biological, psychological, and sociocultural factors of health. The vast literatures of diverse fields - psychology, medicine, public health, social work, and health policy - are integrated by leading scholars, scientists, and practitioners in these areas to explore the impact of South Asian cultural factors on health, health risk, and illness. Chapters incorporate available theoretical and empirical information on the status of chronic health conditions in South Asians in the United States, with consideration of future directions to improve understanding of the health of this group. Cultural and ethnic insights imperative for clinical/community/medical practitioners to provide effective and culturally-appropriate care and treatment from an interdisciplinary lens are provided.